Research of Embedded Tower Crane Monitoring System Based on FCS - Xijian Zheng; Jinbao Zeng; Hong Zhang; Zhengyi Xie (Institute of Advanced Engineering and Science, 2014)
To compensate for the lack of traditional safety limit device of tower crane, a design scheme of embedded tower crane intelligent monitoring system based on Fieldbus Control System was proposed. By this, online collection and transmission of tower crane real-time conditions were achieved, which could effectively improve the reliability and anti-interference of the system. Embedded development technology was used to build ARM-based master control platform. Embedded Linux cross-compiler environment was also built. Combining with embedded programming software, human-computer interaction interface of tower crane intelligent monitoring system was built, storage and display of tower crane’s online parameters were also realized. The use of the technology has opened up a new field of tower crane condition monitoring application. The research of this paper may provide reference for tower crane safety monitoring and fault diagnosing. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4326